Effects of asymmetrical damping on a 2 DOF quarter-car model under harmonic excitation - Silveira, M. [UNESP]; Wahi, P.; Fernandes, J. C.M. [UNESP] (Elsevier, 2017)
The objective of this work is to study the dynamical behavior of vehicle suspension systems employing asymmetrical viscous damping, with a focus on improving passenger comfort. Previous studies have shown that the use of asymmetrical dampers in these types of systems can be advantageous with regard to comfort of the passengers. The modeling and the behavior of a quarter-car model with asymmetrical viscous damping under harmonic excitation is presented. The response is obtained with an analytical approximation via the method of Harmonic Balance. The choice of the asymmetry ratio diminishes the effects that the uneven road causes on the displacement and acceleration of the sprung mass. Although current systems usually adopt larger damping during the expansion phase, it is shown in this work that, for lower frequencies, smaller damping in this phase results in better comfort.
Keywords: Asymmetrical damper; Comfort performance; Harmonic balance; Passenger vehicles